Comparison of Different Approaches to Surface Functionalization of Biodegradable Polycaprolactone Scaffolds - Permyakova, Elizaveta S; Kiryukhantsev-Korneev, Philipp V; Gudz, Kristina Yu; Konopatsky, Anton S; Polčak, Josef; Zhitnyak, Irina Y; Gloushankova, Natalia A; Shtansky, D V; Manakhov, Anton M (Nanomaterials (Basel, Switzerland), 2019)
Due to their good mechanical stability compared to gelatin, collagen or polyethylene glycol nanofibers and slow degradation rate, biodegradable poly-ε-caprolactone (PCL) nanofibers are promising material as scaffolds for bone and soft-tissue engineering. Here, PCL nanofibers were prepared by the electrospinning method and then subjected to surface functionalization aimed at improving their biocompatibility and bioactivity. For surface modification, two approaches were used: (i) COOH-containing polymer was deposited on the PCL surface using atmospheric pressure plasma copolymerization of CO2 and C2H4, and (ii) PCL nanofibers were coated with multifunctional bioactive nanostructured TiCaPCON film by magnetron sputtering of TiC-CaO-Ti3POx target. To evaluate bone regeneration ability in vitro, the surface-modified PCL nanofibers were immersed in simulated body fluid (SBF, 1×) for 21 days. The results obtained indicate different osteoblastic and epithelial cell response depending on the modification method. The TiCaPCON-coated PCL nanofibers exhibited enhanced adhesion and proliferation of MC3T3-E1 cells, promoted the formation of Ca-based mineralized layer in SBF and, therefore, can be considered as promising material for bone tissue regeneration. The PCL-COOH nanofibers demonstrated improved adhesion and proliferation of IAR-2 cells, which shows their high potential for skin reparation and wound dressing.
Keywords: tissue engineering; XPS; plasma modification; mineralization; polycaprolactone nanofibers